Fundamental of Entrepreneurship ENT300 : Secure Plus / Lineker Hamid... [et al.] - Hamid, Lineker; Siam, Rayner; Aselan, Muhammad Fazrul; Fuzael Ghazali, Mohd Zalikh (2011)
The name of our company is SECUREPLUS Sdn Bhd. The business is in the form of partnership which consists of four members. Each partner contributes certain amount of capital as agreed in the agreement. We agreed that Rayner Siam as a General Manager and Administration Manager, Lineker Hamid as a Operation Manager, Muhammad Fazrul Bin Aselan as a Marketing Manager, Mohd Zalik Fuzael Ghazali as a Financial Manager. The selection of General Manager based on the consensus among all the partners and also based on his experiences, skills and abilities.